2020
DOI: 10.1016/j.celrep.2020.108104
|View full text |Cite
|
Sign up to set email alerts
|

An Epilepsy-Associated GRIN2A Rare Variant Disrupts CaMKIIα Phosphorylation of GluN2A and NMDA Receptor Trafficking

Abstract: Highlights d The epilepsy-associated variant GluN2A-S1459G causes NMDAR trafficking defects d GluN2A-S1459G disrupts NMDAR interactions and leads to reduced mEPSC frequency d GluN2A is phosphorylated by CaMKII at S1459, which is regulated by neuronal activity d GluN2A-S1459 phosphorylation dictates binding to PDZ domain-containing proteins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 81 publications
(123 reference statements)
5
45
2
2
Order By: Relevance
“…These data suggest that SNX27 and pseudo-phosphorylated GluN2A are required but not sufficient on their own to drive the endosomal recycling of NMDARs. This is in contrast with results from a recent study, which found that the GluN2A S1459A phospho-deficient mutant causes a slight but significant reduction in the surface expression of NMDARs 28 . This discrepancy could be due to several reasons, including the age and density of the neurons, experimental protocols and method of analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These data suggest that SNX27 and pseudo-phosphorylated GluN2A are required but not sufficient on their own to drive the endosomal recycling of NMDARs. This is in contrast with results from a recent study, which found that the GluN2A S1459A phospho-deficient mutant causes a slight but significant reduction in the surface expression of NMDARs 28 . This discrepancy could be due to several reasons, including the age and density of the neurons, experimental protocols and method of analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Phosphorylation of NMDAR subunits in the C-terminal domain is a common mechanism controlling receptor trafficking and function 25 . A recent study has shown that GluN2A is phosphorylated on its Cterminal domain at Ser-1459 by CaMKIIα both in vitro and in cells 28 , a finding which we confirmed here ( Supplementary Fig. 1).…”
Section: Nmdarssupporting
confidence: 91%
See 3 more Smart Citations